The Invalidity of Foreign Currency Loans in the Hungarian Judicial Practice - Király, Péter Bálint (Public Governance, Administration and Finances Law Review, 2017)
After the economic crisis, a large part of the Hungarian population could not repay the suddenly increased instalments of their foreign currency loans. In lawsuits concerning the invalidity of these foreign currency loans, the different courts interpreted the provisions of the law differently, so the Curia (the highest judicial authority of Hungary) – fulfilling its constitutional duty – considered it necessary to unify the judicial practice. For this purpose, several Uniformity Decision were adopted. In this study I will briefly summarize the content of three Uniformity Decisions, namely, Decision No. 6/2013 PJE, No. 2/2014 PJE and No. 1/2016 PJE.